PENGEMBANGAN PRODUK “COOKIES BIMOCA” BERBASIS UBI JALAR PUTIH, TEPUNG MOCAF, DAN TEPUNG KACANG HIJAU SEBAGAI MAKANAN SELINGAN UNTUK IBU HAMIL KEK (KEKURANGAN ENERGI KRONIS) - Fauziyah, Roro Nur; Isdiany, Nitta; Gumilar, Mulus; Pratiwi, Nur Febrianty Putri (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
Indonesia is facing a complex nutritional problem (double burden malnutrition) which is increasing every year. The high rate of Chronic Energy Deficiency (CED), namely in non-pregnant mother the CED rate is 14.4% and 17.3% in pregnant mother. Chronic Energy Deficiency is a long-lasting lack of energy intake characterized by an upper arm circumference (LILA) <23.5 cm. The main cause of CED in pregnant mother is the lack of energy intake obtained by pregnant mother, so efforts need to be made to overcome CED by providing high-energy snacks in the form of cookies. Sweet potatoes, mocaf flour and green bean flour are added as cookie ingredients which can increase energy and protein content for pregnant mother who experience chronic energy deficiency (CED). This research aims to determine the effect of white sweet potato, mocaf flour, and green bean flour on the quality of cookies that meet dietary requirements and organoleptic properties. This research is an experimental research with a comparative formulation of mocaf flour and green bean flour F1 80% : 20%, F2 60% : 40%, and F3 50% : 50%. The organoleptic test was carried out by 25 untrained panelists using the hedonic test method with 7 scales. Data analysis used the Kruskal Wallis test. The cookies that have the highest level of preference are the F3 formula with a ratio of mocaf flour and green bean flour of 50%: 50%, one serving size of 60 grams (4 pieces) which can fulfill around 113% -117% of the energy needs of pregnant mother's snacks. The statistical test results showed that there were no significant differences between the three BIMOCA cookies formulations because the p value was > 0.05.